Pain Management for Nonsyndromic Craniosynostosis: Adequate Analgesia in a Pediatric Cohort?. Issue 5 (July 2018) - Kattail, Deepa; Macmillan, Alexandra; Musavi, Leila; Pedreira, Rachel; Faateh, Muhammad; Cho, Regina; Lopez, Joseph; Dorafshar, Amir H.
Abstract : Background: Postoperative pain following open craniosynostosis repair has not been studied extensively and is sometimes thought to be inconsequential. The purpose of this study was to assess postoperative pain in this pediatric population. Methods: We performed a retrospective chart review of patients (n = 54) undergoing primary open craniosynostosis repair from 2010 to 2016. Demographics, length of stay (LOS), pain scores, emesis events, and perioperative analgesics were reviewed. Multivariable regression models were designed to assess for independent predictors of LOS and emesis. Results: A high proportion had moderate to severe pain on postoperative day 0 (56.5%) and day 1 (60.9%). Opioid administered in postoperative period was 1.40 mg/kg/d in morphine milligram equivalent (MME) (±1.07 mg/kg/d MME). Majority of patients transitioned to enteral opioids on postoperative day 1 (24.5%) or day 2 (49.1%). Ketorolac was administered to 11.1% (n = 6). Emesis was documented in 50% of patients. LOS revealed a positive association with age ( P = 0.006), weight ( P = 0.009), and day of transition to enteral opioids ( P < 0.001); association with emesis was trending toward significance ( P = 0.054). There was no association between overall LOS and amount of opioids administered postoperatively ( P = 0.68). Postoperative emesis did not have any significant association with age, sex, weight, total amount of postoperative opioid administered, use of ketorolac, or intraoperative steroid use. Conclusion: Open craniosynostosis repair is associated with high levels of pain and low utilization of nonopioid analgesics. Strategies to improve pain, decrease emesis and LOS include implementation of multimodal analgesia period and avoidance of enteral medications in the first 24 hours after surgery.